The Influence of Service Quality and Facilities on Consumer Satisfaction of Mie Gacoan Karawang - Zenita Apriani, Zenita Apriani; Yudha Rahman, Shandikha Arya; Yani, Dini; Rosmawati, Ery (Yayasan Pendidikan Belajar Berdikari, 2023)
In this modern era, there is a lot of progress in the business world. Competition is so tight that every manufacturer continues to develop its business to win the competition. Service quality is a strategy used by companies to retain and attract consumers. For business people, providing superior service is a very important strategy because it can generate more new consumers. . Apart from the quality of service, facilities also play an important role in influencing consumer satisfaction so that consumers will continue to come back to the Mie Gacoan branch because it has facilities such as a comfortable place. This research aims to find out how the quality of service and facilities affects consumer satisfaction at Mie Gacoan Karawang Branch. The population used was 52 consumers. The analysis technique used is multiple regression analysis using SPSS. The research results show that the quality of service and facilities influences consumer satisfaction.